Pengaruh Corporate Governance Terhadap Manajemen Pajak - Wastam Wahyu Hidayat; Soehardi Soehardi; Cahyadi Husadha (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This research aims to determine the influence of the number of Commissioners, the percentage of independent commissioners, and the compensation of the Board of Commissioners and the directors on tax management. A sample of one of the ten companies in the manufacturing sector listed on the Indonesia Stock Exchange during 2014-2018 using the Purposive sampling method. The study used multiple linear regression analysis techniques with SPSS aids (Statistical Product and Service Solutions). The results of the partial study showed that the number of Commissioners (BOARD) was positively influential in the tax management (ETR) while the percentage of independent commissioners (INDEP) and the compensation of the BOC and the Board of Directors (COMP) did not affect the tax management (ETR).